THE ROLE OF ADMINISTRATIVE SANCTIONS IN ENVIRONMENTAL PROTECTION IN INDONESIA - Rolando Marpaung; Dikki Saputra Saragih; Micael Jeriko Damanik; Putri Hutasoit (Journal of International Islamic Law, Human Right and Public Policy, 2023)
This research aims to find out how administrative sanctions are applied in efforts to protect and manage the environment in Indonesia and what factors hinder the implementation of these sanctions. This research uses respectful legal research methods and achieves the following objectives: 1. Administrative sanctions in efforts to protect and manage the environment: written warnings, government coercion, freezing of environmental permits, revocation of environmental permits, and administrative fines imposed by the government without going through court proceedings against the perpetrators businesses or activities that violate environmental administration provisions. Administrative sanctions are used to prevent violations and enable the government to stop such violations and allow the government to stop such violations. 2. Legal regulations and law enforcement agencies prevent the application of administrative sanctions in efforts to protect and manage the environment. There are no guidelines for implementing administrative sanctions that regulate how fines are determined and how much fines are imposed for delays in implementing government coercion, so people are free to decide for themselves. This also applies to different law enforcement agencies that have the authority to apply administrative sanctions in environmental cases.